2017
DOI: 10.1177/0267323117710900
|View full text |Cite
|
Sign up to set email alerts
|

What have I done to deserve this? The role of deservingness in effects of ordinary citizens as cases in the news

Abstract: Previous studies have shown that cases in news reporting have substantial attitudinal effects on the audience. The direction of results has been mixed, however. Some studies reported that news audience change opinion in favour of the position of the case, while other studies reported the opposite. In this article, we emphasize the deservingness of cases as a potential factor explaining the differences in previous results. In two population-based survey experiments, we empirically investigate how exposure to ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 38 publications
0
15
0
1
Order By: Relevance
“…One characteristic of persons at the receiving end of policy decisions, which has repeatedly been shown to influence people’s reactions toward these people, is how much they deserve the help (e.g., Aarøe and Petersen 2014; Petersen 2012). A recent study suggests that the degree of deservingness of an exemplar drives opinions on the welfare benefit received by the group that the exemplar represents (Hopmann et al 2017). Thus, people are willing to support policies in favor of exemplars, but only if they find them deserving.…”
Section: Discussionmentioning
confidence: 99%
“…One characteristic of persons at the receiving end of policy decisions, which has repeatedly been shown to influence people’s reactions toward these people, is how much they deserve the help (e.g., Aarøe and Petersen 2014; Petersen 2012). A recent study suggests that the degree of deservingness of an exemplar drives opinions on the welfare benefit received by the group that the exemplar represents (Hopmann et al 2017). Thus, people are willing to support policies in favor of exemplars, but only if they find them deserving.…”
Section: Discussionmentioning
confidence: 99%
“…Aarøe (2011) and Boukes et al (2015) found that episodically framed news stories are more likely to cause support for governmental policies that benefit the exemplified persons in a news story than thematically framed news. Other studies found mixed or insignificant effects (Ben-Porath and Shaker 2010;Feezell et al 2019;Hopmann et al 2017;M. Kim et al 2020;Krupnikov and Levine 2019;Ostfeld and Mutz 2014).…”
Section: Framing and Its Effect On Attributions Of Responsibility: A Mixed Picturementioning
confidence: 95%
“…The literature on the effects of episodic and thematic framing is dominated by a mixture of findings (Krämer and Peter 2020). Recent studies pointed out message features (issue salience, see Ciuk and Rottman 2020; or topic, see Feezell et al 2019) and exemplar characteristics (deservingness, see Hopmann et al 2017; and similarity, see Ostfeld and Mutz 2014) that could moderate the effects, and thus explain opposite results. One aspect of Markus and Zajonc's (1985) Orientations-Stimulus-Orientations-Response (O-S-O-R) model, however, requires more attention to understand the conditional nature of episodic and thematic framing effects (see, e.g., Ben-Porath and Shaker 2010; M. Kim et al 2020): The differences between people (i.e., "Orientations") consuming the news may determine with which cognitive schema a frame resonates on the individual level and, thus, how the message is interpreted and, eventually, what effects will occur.…”
Section: Conditionality Of Framing Effects Upon Political Ideologymentioning
confidence: 99%
“…In this vein, Hopmann, Skovsgaard, and Elmelund-Praestekaer (2017) argue that findings about the importance of audience similarity may actually mask the operation of pervasive assumptions about who is socially deserving. Again, we come back to the power of the background stories and stereotypes in terms of which a given story is interpreted.…”
Section: Stories' Audiences: Who Is "Like" the Protagonist?mentioning
confidence: 99%